Ultrasound‐Guided Hydraulic Release Associated With Corticosteroids in Radial Tunnel Syndrome: Description of Technique and Preliminary Clinical Results. (3rd July 2019) - García, Nicolás; Rosales, Julio; Greene, Cristóbal; Droppelmann, Guillermo; Verdugo, Marco A.
Abstract : The aim of this study was to describe a perineural ultrasound‐guided infiltration technique for management of radial tunnel syndrome and to report its preliminary results in 54 patients. A mixture of a saline solution, a local anesthetic, and a corticosteroid solution was infiltrated in the perineural region at the arcade of Frohse. Pain was reported in 100% of patients before the procedure versus 1.9% after the procedure. Scratch collapse and Cozen test results were positive in 98.1% and 66.7% of patients before infiltration, respectively, versus 5.6% and 9.2% after infiltration. All variables had statistically significant differences between preprocedure and postprocedure evaluations ( P  < .01).